Physical Inactivity Is Associated With Increased Levels of Anxiety, Depression, and Stress in Brazilians During the COVID-19 Pandemic: A Cross-Sectional Study - Silva, Lucas Raphael Bento; Seguro, Camila Simões; de Oliveira, Camila Grasiele Araújo; Santos, Paulo Otávio Silva; de Oliveira, Jordana Campos Martins; de Souza Filho, Luiz Fernando Martins; de Paula Júnior, Célio Antônio; Gentil, Paulo; Rebelo, Ana Cristina Silva (Frontiers in Psychiatry, 2020)
Objective: to evaluate the levels of anxiety, depression and stress associated with the practice of physical exercise (PE) during pandemic by COVID-19. Methods:This study has a cross-sectional characteristic and was carried out between May 12 and 14, 2020. An online questionnaire was applied with questions to assess sociodemographic characteristics and physical exercise during the CoVID-19 pandemic, in addition to depression, anxiety and stress analysis. The study was approved by the local ethics committee (CAAE: 31521720.8.0000.5082). Results: 1154 answered the questionnaire (69.84% female). During the isolation period, the number of participants who declared not to exercise was 54.16%. Women generaly presented higher levels of anxiety, depression and stress when compared to men (p <0.0001 for all domains). The risk of having increased anxiety were 118% higher (OR = 2.183; 95% CI = 1.717 – 2.775), the risk of depression was 152% higher (OR = 2.525; 95% CI = 1.991 – 3.205) and the risk of stress symptoms increased 75.1% (OR = 1.751; 95% CI = 1.386 – 2.213) in the participants who did not perform PE when compared to those who maintain regular PE. Conclusion: people who was not involved with PE during the COVID-19 pandemic had higher anxiety, depression and stress scores. Based on this, it seems important to advise people to continue PE, following all the recommendations of preventive measures of the pertinent health organizations.